Upaya Meningkatkan Hasil Belajar Peserta Didik pada Muatan Matematika Materi Jam Kelas II SD Negeri 08 Mataram melalui Model Pembelajaran Project Based Learning - Aini, Nurul; Darmiany, Darmiany (TSAQOFAH, 2023)
The aim of this research is to improve student learning outcomes in the cognitive domain through the application of the Project Based Learning (PJBL) learning model. This type of research is classroom action research. Data collection methods use interviews and documentation. The type of data used is qualitative data and quantitative data. The subjects in this research were class 2 students at SDN 08 Mataram, totaling 28 students. The results of the research showed that there was an increase in the percentage of student learning outcomes, namely in the pre-cycle the percentage was 72% with the sufficient category (C), then in the first cycle it increased to 77% with the sufficient category (C) and increased to 83% in the second cycle with the good category (B ) which means that the use of the Project Based Learning learning model is effective in improving the learning outcomes of class 2 students at SDN 08 Mataram.